Correlation and agreement between superb micro-vascular imaging and contrast-enhanced ultrasound for assessing radiofrequency ablation treatment of thyroid nodules: a preliminary study - Yu Lan (BMC, 2021)
Abstract Background To evaluate the correlation and agreement between superb micro-vascular imaging (SMI) mode and the contrast-enhanced ultrasound (CEUS) mode for the ablative completeness and the volumes of ablation lesions to determine the clinical application value of SMI in follow-up after radiofrequency ablation. Methods From April 2020 to June 2020, two radiologists used SMI and CEUS mode to measure the volume of the ablation lesion. We use intra-class correlation coefficient (ICC), scatter plots and Bland–Altman plots to evaluate the correlation and agreement of the two techniques. In addition, intra- and inter-observer reliability in volume measurement of ablation lesions with SMI mode was assessed. Results SMI mode and CEUS mode have good agreement in the evaluation of ablative completeness. The ICC was 0.876 and 0.928 of reader A and reader B between SMI mode and CEUS mode in terms of ablation lesions volume measurement. There was a strong correlation between the two modes in both reader A and reader B (rA = 0.808; rB = 0.882). The ICC was 0.836 for the inter-observer reliability of SMI technique. The scatter plot showed a good linear relation (r = 0.715). In the Bland–Altman plot, 4.35% (1/23) of the points was outside the 95% limits of agreement. The ICC was 0.965 for the intra-observer reliability of SMI technique, the scatter plot also showed a strong linear correlation (r = 0.965). In the Bland–Altman plot, 8.70% (2/23) of the points was outside the 95% limits of agreement. Conclusions SMI and CEUS have good agreement and correlation in the ablation volume measurement. SMI technology is expected to be applied as an alternative to CEUS in the clinical follow-up of ablation lesions.